Enhancing the shelf-life of papaya (var. Red lady) through essential oils and probiotics by mitigating fruit rot - Anagha L. G.; Ramesh G.; Kurubar A. R.; Patil S. S.; Ajithkumar K.; Nagaraj M. N. (Journal of Tropical Agriculture, 2025)
A study to know the effect of essential oils and probiotics in enhancing the shelf life of papaya cv. Red Lady was conducted in two consecutive years (2023 and 2024). The study consisted of seven treatments with three replications, each with six fruits. Among the seven treatments, tulsi oil (2.5%) significantly, increased the shelf-life, exhibited lower total soluble sugars (TSS), reducing sugar and total sugar during 10 days of storage of papaya fruits, whereas, ginger oil (2%) lowered physiological loss in weight and exhibited higher fruit firmness. The performance of probiotics, viz., Lactobacillus fermentum AM1 and L. plantarum B1 in enhancing shelf life was not pronounced, when compared to the essential oils used in the study. Organoleptic evaluation has revealed that the fruits treated with ginger oil (2%) had better color, flavor, texture, and overall acceptance. Minimum fruit rot incidence was observed in fruits treated with ginger oil (2%) on 7th and 10th day of storage. Preharvest spray of papaya fruits with tulsi oil (2.5%) 15 days before breaker stage will help in enhancing the shelf life.